An Environmentally Relevant Mixture of Perfluorooctanesulfonic Acid and Perfluorohexanesulfonic Acid Does Not Conform to Additivity in Northern Leopard Frogs Exposed Through Metamorphosis. (2nd November 2022) - Hoskins, Tyler D.; Allmon, Elizabeth B.; Flynn, R. Wesley; Lee, Linda S.; Choi, Youn; Hoverman, Jason T.; Sepúlveda, Maria S.
Abstract: Per‐ and polyfluoroalkyl substances (PFAS) are chemicals associated with adverse health effects. At aqueous film–forming foam sites, they occur as mixtures, with perfluorooctanesulfonic acid (PFOS) and perfluorohexanesulfonic acid (PFHxS) commonly co‐occurring in the highest concentrations. Although PFOS and PFHxS toxicities have been studied, few studies have tested their potential interaction. Using Rana pipiens, the present study compared toxicities of a 1:1 PFOS:PFHxS mixture to PFOS and PFHxS individually with the prediction that responses would be additive. Gosner stage 25 (GS 25) tadpoles were exposed through metamorphosis (GS 46) to 0.5 and 1 ppb PFOS or PFHxS alone or to a mixture of 0.5 ppb PFOS and 0.5 ppb PFHxS. Tadpoles were weighed and measured (snout‐vent length [SVL]) at day 31, metamorphic climax (GS 42), and GS 46. These values were used to calculate the scaled mass index (SMI), a measure of body condition. Body burdens were quantified on day 31 and at GS 46. The PFOS and PFHxS body burdens were elevated relative to controls at GS 46. No effects were observed on survival, SVL, or mass. Single PFAS effects included a 17% reduction in SMI at day 31 (0.5 ppb PFHxS) and a 1.1‐day longer metamorphic period (1 ppb PFHxS) relative to controls. Mixture results deviated from additivity—SMIs were higher than expected on day 31 and lower than expected at GS 42. In addition, time to GS 42 in the PFAS mixture exceeded expected additivity by 12 days. Results from a chronic exposure to a 1:1 PFOS:PFHxS mixture resulted in changes in body condition and length of metamorphosis that deviated from additivity. More PFAS mixture toxicity studies conducted at relevant ratios and concentrations are needed. Environ Toxicol Chem 2022;41:3007–3016. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.